Eksplorasi Metabolit Sekunder dari Spons di Wilayah Sulawesi Selatan dan Uji Bioaktivitasnya terhadap Artemia salina - Beddu Jawahir; Nunuk Hariani Soekamto; Rosmawaty Rosmawaty (Hasanuddin University, 2009)
Abstract. Explorations of secunder metabolic, especially non active fraction of Clathria reinwardtii, of spons from South Sulawesi have been done. Bioactivity test against Artemia salina was carried out with Brine Shrimp Lethality Test method. Separation techniques contain of extraction, fractionation, and purification. Qualitative tests and structure elucidation on the compound obtained was based on the physical and spectroscopic data UV, IR and NMR. Two compounds which are isolated from Clathria reinwardtii are suggested as fenolic compound and steroid group i.e. β-sitosterol.Keywords : β-sitosterol, Artemia salina Leach, Clathria reinwardtii, fenolic.